2017
DOI: 10.1177/1932202x17740331
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Gender Gaps in English Composition and College Algebra in College: The Mediating Role of Psychosocial Factors

Abstract: We examined the role of six psychosocial factors (PSFs) in explaining gender gaps in English Composition (n = 8,633) and College Algebra (n = 2,261) using data of first-year female (55%) and male students from 42 colleges. Using a multilevel model and controlling for prior achievement, we found that PSFs mediated between 3% and 41% of the gender gap in English Composition, but only one PSF (Academic Discipline), helped explain the gender gap in College Algebra. Gender gaps significantly narrowed when students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
(151 reference statements)
0
3
1
Order By: Relevance
“…This is contrary to previous research into gender differences The skill of discipline across many fields (e.g. Mattern et al, 2017;Ndum et al, 2018) but is in line with a study of successful business students, which reported no significant differences between performance of women and men in business master programs (Eddey and Baumann, 2009). In contrast, an interesting pattern emerged when each of the countries was examined separately.…”
Section: Discipline Levels Across Gendercontrasting
confidence: 64%
See 1 more Smart Citation
“…This is contrary to previous research into gender differences The skill of discipline across many fields (e.g. Mattern et al, 2017;Ndum et al, 2018) but is in line with a study of successful business students, which reported no significant differences between performance of women and men in business master programs (Eddey and Baumann, 2009). In contrast, an interesting pattern emerged when each of the countries was examined separately.…”
Section: Discipline Levels Across Gendercontrasting
confidence: 64%
“…For example, Mattern et al (2017) investigated the role that academic discipline plays in the college admissions process in predicting firstyear GPA by gender and found that female students had a higher level of discipline. In addition, in a study investigating gender gaps in English and mathematics of first-year college students, Ndum et al (2018) concluded that male students could benefit from targeted programs aimed at increasing academic discipline more than females.…”
Section: Gendermentioning
confidence: 99%
“…In addition, in a systematic review of 23 studies examining the relationship between gender and school achievement in the United Kingdom between 2000 and 2012 utilising data from the three-yearly Programme for International Student Assessment (PISA) (Early et al, 2020), gender was found to be a predictor of achievement, with girls achieving greater scores in reading than boys across the five PISA cycles whilst boys were reported to outperform girls in math, also in all five cycles of PISA. In a study into gender gaps in college English composition and algebra in the United States of America, females were found to score higher in both courses than male students (Ndum et al, 2018).…”
Section: Gendermentioning
confidence: 98%
“…, 2020), gender was found to be a predictor of achievement, with girls achieving greater scores in reading than boys across the five PISA cycles whilst boys were reported to outperform girls in math, also in all five cycles of PISA. In a study into gender gaps in college English composition and algebra in the United States of America, females were found to score higher in both courses than male students (Ndum et al. , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%